Analisis Standar Sarana dan Prasarana di Yayasan Perguruan RA Al-Kamal - Fauziah Nasution; Intan Puspita Sari; Risa Ummah Pratiwi; Zahra Yunita; Irma Qurata Aini; Supia Supia (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Facilities and infrastructure are an important part of the educational process. In order for students' educational efforts to produce the desired learning outcomes, certain conditions need to be met. Student achievement can always be improved by paying attention to the many things that motivate students to learn effectively. This can be enhanced if one has access to high-quality learning resources and is able to use them effectively. To meet these expectations, it is necessary to use teaching methods that involve students more actively in the learning process. As a teacher candidate for the Faculty of Tarbiyah and Teacher Training (FITK) as a unit of the State Islamic University of North Sumatra. Therefore, FITK UIN Sumut implements an apprenticeship program in stages for fifth semester students. By holding this activity, it is hoped that the apprentice program participants will have the attitude, understanding, appreciation of motivation and skills as socially competent prospective teachers, and in time have the attitude of becoming professional and competent teacher. The Ra Al-kamal Education Foundation School is the school of choice for which the standard of educational facilities and infrastructure will be observed. This study uses a qualitative descriptive approach to collect data on the use and maintenance of educational resources in schools. Researchers can obtain a clearer picture of the phenomena and facts related to their research subjects by using qualitative research strategies. Keywords: RA AL-Kamal, Facilities, Educational Infrastructure.